1988
DOI: 10.1007/bf01655880
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of pylorus preservation during pancreaticoduodenectomy

Abstract: Although pyloric preservation can be performed during pancreaticoduodenectomy without increased morbidity or mortality or decreased survival, the long-term benefit of this technique remains unproven. In this study, the functional status of patients recovered from pyloric-preserving pancreaticoduodenectomy was evaluated by comparing 6 long-term survivors of the standard Whipple procedure (1-7 years postoperative; mean. 4.7 yr) to a similar group of 6 patients recovered from pylorus preservation pancreaticoduode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 46 publications
1
48
0
1
Order By: Relevance
“…(5) Still there is some concern of delayed gastric emptying in pylorus-pre serving technique based on early publications. Recent data, however, do not any longer continue to support this finding but show an equal occurrence rate of delayed gas- trie emptying between the pylorus-preserving duodeno pancreatectomy and the standard Whipple [23][24][25]. The reason for this may again be the careful preservation of pyloric innervation and perfusion.…”
Section: Advantages and Disadvantagesmentioning
confidence: 84%
“…(5) Still there is some concern of delayed gastric emptying in pylorus-pre serving technique based on early publications. Recent data, however, do not any longer continue to support this finding but show an equal occurrence rate of delayed gas- trie emptying between the pylorus-preserving duodeno pancreatectomy and the standard Whipple [23][24][25]. The reason for this may again be the careful preservation of pyloric innervation and perfusion.…”
Section: Advantages and Disadvantagesmentioning
confidence: 84%
“…24,33 As a result, emptying of liquids takes a significantly shorter time after PPPD than after Whipple resection. 34,35 Likewise, physiologic measurements of serum gastrin have been shown to be nearly normal after PPPD but markedly depressed after standard Whipple (in which antrectomy removes the source of gastrin). 21,36 Other, more ambitious studies have failed to demonstrate nutritional advantages in terms of glucose homeostasis and iron absorption.…”
Section: Discussionmentioning
confidence: 99%
“…21,36 Other, more ambitious studies have failed to demonstrate nutritional advantages in terms of glucose homeostasis and iron absorption. 34 In general, most studies have used postoperative patient weights as parameters of nutritional status and have reported weight gain in 67% to 95% of patients after PPPD. 13,16,37,38 Our data, however, demonstrate no differences in nutritional parameters between the two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al [38] reported an endoscopic or radiologic diagnosis of ulcers in 6 of 126 patients (5%). Fink et al [39] also found a 5% incidence of marginal ulceration in a follow-up of 40 patients. Higher incidences of 10-19% are reported by other authors in follow-up studies 30-60 months after the pylorus-preserving Whip ple [26,[30][31][32].…”
Section: Introductionmentioning
confidence: 94%